Russian Fiddler Tales from Romania about Russia (2021-2022) - NAE, Adrian (2024)
The main character of this collection of academic papers and essays is Russia. Not just the country, but its top leaders – Putin included – and their incredible way of substituting known reality with clinical, pathological political fantasies, while replacing rationality with a bellicose will, that would hardly escape from a comparison with Hitler’s ill-fated ambitions from before 1945. It is a book that speaks not only of what international relations nowadays mean, after pocketing Crimea in 2014 and invading Ukraine eight years after. Dr. Adrian Nae endeavoured to provide us with academic, i.e. competent, analyses about Russia’s strategic objectives and plans, domestic policies, popular mentalities and propaganda mechanisms and effects.